Laser particle activated cell sorting in microfluidics. Issue 12 (27th May 2022) - Dannenberg, Paul H.; Kang, Jisoo; Martino, Nicola; Kashiparekh, Anokhi; Forward, Sarah; Wu, Jiamin; Liapis, Andreas C.; Wang, Jie; Yun, Seok-Hyun
Abstract : A microfluidic device is developed that uses the narrowband optical radiation of laser particle barcodes to sort tagged cells. Abstract : Laser particles providing bright, spectrally narrowband emission renders them suitable for use as cellular barcodes. Here, we demonstrate a microfluidic platform integrated with a high-speed spectrometer, capable of reading the emission from laser particles in fluidic channels and routing cells based on their optical barcodes. The sub-nanometer spectral emission of each laser particle enables us to distinguish individual cells labeled with hundreds of different laser colors in the near infrared. Furthermore, cells tagged with laser particles are sorted based on their spectral barcodes at a kilohertz rate by using a real-time field programmable gate array and 2-way electric field switch. We demonstrate several different flavors of sorting, including isolation of barcoded cells, and cells tagged with a specific laser color. We term this novel sorting technique laser particle activated cell sorting (LACS). This flow reading and sorting technology adds to the arsenal of single-cell analysis tools using laser particles.